Effect of endoscopic transpapillary biliary drainage with/without endoscopic sphincterotomy on post-endoscopic retrograde cholangiopancreatography pancreatitis in patients with biliary stricture (E-BEST): a protocol for a multicentre randomised controlled trial. Issue 8 (11th August 2017) - Kato, Shin; Kuwatani, Masaki; Sugiura, Ryo; Sano, Itsuki; Kawakubo, Kazumichi; Ono, Kota; Sakamoto, Naoya
Abstract : Introduction: The effect of endoscopic sphincterotomy prior to endoscopic biliary stenting to prevent post-endoscopic retrograde cholangiopancreatography pancreatitis remains to be fully elucidated. The aim of this study is to prospectively evaluate the non-inferiority of non-endoscopic sphincterotomy prior to stenting for naïve major duodenal papilla compared with endoscopic sphincterotomy prior to stenting in patients with biliary stricture. Methods and analysis: We designed a multicentre randomised controlled trial, for which we will recruit 370 patients with biliary stricture requiring endoscopic biliary stenting from 26 high-volume institutions in Japan. Patients will be randomly allocated to the endoscopic sphincterotomy group or the non-endoscopic sphincterotomy group. The main outcome measure is the incidence of pancreatitis within 2 days of initial transpapillary biliary drainage. Data will be analysed on completion of the study. We will calculate the 95% confidence intervals (CIs) of the incidence of pancreatitis in each group and analyse weather the difference in both groups with 95% CIs is within the non-inferiority margin (6%) using the Wald method. Ethics and dissemination: This study has been approved by the institutional review board of Hokkaido University Hospital (IRB: 016–0181). Results will be submitted for presentation at an international medical conference and published in a peer-reviewed journal. Trial registration number: The University Hospital Medical Information Network ID: UMIN000025727 Pre-results.